2013
DOI: 10.1088/0004-637x/768/2/186
|View full text |Cite
|
Sign up to set email alerts
|

Uhecr Escape Mechanisms for Protons and Neutrons From Gamma-Ray Bursts, and the Cosmic-Ray-Neutrino Connection

Abstract: The paradigm that gamma-ray burst (GRB) fireballs are the sources of the ultra-high energy cosmic rays (UHECRs) is being probed by neutrino observations. Very stringent bounds can be obtained from the cosmic ray (proton)-neutrino connection, assuming that the UHECRs escape as neutrons. In this study, we identify three different regimes as a function of the fireball parameters: the standard "one neutrino per cosmic ray" case, the optically thick (to neutron escape) case, and the case where leakage of protons fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 53 publications
3
118
0
Order By: Relevance
“…Another important aspect is that the relationship between neutrino and cosmic-ray emission depends on the UHECR escape mechanism (Baerwald et al 2013). It has been shown that, depending on the parameter values, a fraction of cosmic rays must directly escape from the sources without neutrino production (Baerwald et al 2013).…”
Section: One-zone Versus Multi-zone Emissionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another important aspect is that the relationship between neutrino and cosmic-ray emission depends on the UHECR escape mechanism (Baerwald et al 2013). It has been shown that, depending on the parameter values, a fraction of cosmic rays must directly escape from the sources without neutrino production (Baerwald et al 2013).…”
Section: One-zone Versus Multi-zone Emissionmentioning
confidence: 99%
“…The maximum proton energy ¢ E p,max is computed by balancing the acceleration rate, and the synchrotron, adiabatic, and photohadronic energy loss rates (Baerwald et al 2013).…”
Section: Simulating Collisions In a Grb Jetmentioning
confidence: 99%
See 3 more Smart Citations